The health risks and benefits of cycling in urban environments compared with car use: health impact assessment study. (4th August 2011) - Rojas-Rueda, David; de Nazelle, Audrey; Tainio, Marko; Nieuwenhuijsen, Mark J
Abstract : Objective To estimate the risks and benefits to health of travel by bicycle, using a bicycle sharing scheme, compared with travel by car in an urban environment. Design Health impact assessment study. Setting Public bicycle sharing initiative, Bicing, in Barcelona, Spain. Participants 181 982 Bicing subscribers. Main outcomes measures The primary outcome measure was all cause mortality for the three domains of physical activity, air pollution (exposure to particulate matter <2.5 µm), and road traffic incidents. The secondary outcome was change in levels of carbon dioxide emissions. Results Compared with car users the estimated annual change in mortality of the Barcelona residents using Bicing (n=181 982) was 0.03 deaths from road traffic incidents and 0.13 deaths from air pollution. As a result of physical activity, 12.46 deaths were avoided (benefit:risk ratio 77). The annual number of deaths avoided was 12.28. As a result of journeys by Bicing, annual carbon dioxide emissions were reduced by an estimated 9 062 344 kg. Conclusions Public bicycle sharing initiatives such as Bicing in Barcelona have greater benefits than risks to health and reduce carbon dioxide emissions.